Vascular Malformations and Intractable Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
A retrospective study of 20 consecutive patients with cerebral vascular malformations who were treated surgically for medically refractory partial epilepsy is reported from the Departments of Neurology and Neurologic Surgery, Mayo Clinic, Rochester, MN.